Pedogenic and biogenic alkaline‐extracted silicon distributions along a temperate land‐use gradient. (15th August 2014) - Barão, L.; Clymans, W.; Vandevenne, F.; Meire, P.; Conley, D. J.; Struyf, E.
Summary The primary source of dissolved silicon (Si: DSi) is the weathering of silicate minerals. In recent years, it has been shown that Si cycling through vegetation creates a more soluble Si pool in the soil, as amorphous Si (ASi) deposits in plants (phytoliths) are returned to the soil through litter. Amorphous Si accumulation in soils depends on a number of factors, including land use. In addition to the biogenic ASi fraction, soils contain other non‐biogenic amorphous and sorbed Si fractions that could contribute significantly to DSi export to rivers, but hitherto these Si fractions have been difficult to separate from each other with traditionally applied extraction methods. The objective of this paper is to understand better how land use affects the distribution of the different extractable Si fractions. We re‐analysed samples from the land‐use gradient studied previously by Clymans et al. (2011) with a continuous Si and aluminium (Al) extraction technique. Different extractable Si fractions of biogenic or pedogenic origin were successfully separated on the basis of their dissolution in alkaline solutions (Na2CO3 and NaOH) and Si:Al ratios. We show that forests store almost all alkaline extractable Si (AlkExSi) in the pedogenic fraction while the importance of phytoliths increases with human disturbance to become the dominant fraction in the AlkExSi pool at the arable site. The pedogenic AlkExSi pool is also more reactive than the phytolith‐bound Si. Conversely, pastures and croplands tend to preserve phytoliths in the soil, which are less reactive, decreasing the potential of DSi export relative to forested ecosystems.